The Rise and Fall of the Labour Party in Alberta, 1917-42 - Finkel, Alvin (Labour / Le Travail, 1985)
While Alberta is generally regarded as a conservative province, its early labour movement was class conscious and, for many years had a significant political impact provincially and in many municipalities. The Labour Party, which united trade unions and socialists of every stripe (until its expulsion of the Communists in 1929) reflected the determined independence of Alberta workers: its leaders and members were almost exclusively working-class. But the party was always an uneasy alliance between those who saw politics purely in electoral terms and those who emphasized extra-parliamentary activity. And the election in 1921 of a Farmers' government caused divisions about how closely Labour should work with a non-Labour government. After the purge of the Communists, those who favoured an exclusive concentration on electoral activity and close collaboration with the Farmers, held sway. Their narrow conception of politics turned the Labour Party increasingly into a private preserve of union bureaucrats and created a political vacuum into which Social Credit stepped in.
Keywords: ALLIANCES (International relations); Alberta; Communists; Farmers; LABOR parties; Labor Unions; Labor movement; SOCIALISTS; Working class